Left Ventricular Thrombus of Unknown Etiology in a Patient With COVID-19 Disease With No Significant Medical History - Russell, Joseph; Wagoner, Michael; DuPont, James; Myers, Douglas; Muthu, Krishnakumar; Thotakura, Sudhir (Cardiovascular revascularization medicine, 2022)
The incidence of left ventricular thrombus is relatively low. Ventricular thrombi typically manifest in patients with reduced ejection fraction and post myocardial infarction [1]. The impact of COVID-19's hypercoagulability state is presented here. A 44 year old male who contracted COVID-19, progressed to moderate disease requiring inpatient treatment with supplemental oxygen. During the course of the hospital stay, while receiving National Institutes of Health guideline directed thromboembolism prophylaxis for COVID-19 infected patients [2], the patient developed a left ventricular thrombus which consequently embolized and occluded the left anterior descending and left circumflex coronary arteries requiring rheolytic thrombectomy. •Seemingly healthymale adult contracts COVID-19 becomes hospitalized for respiratory failure due to moderate-severe COVID disease•While on guideline directed venous thromboembolism prophylaxis, patient develops left ventricular thrombus•Emboli from thrombous occlude left anterior descending coronary artery and near-occlude left circumflex coronary artery•Patient requires mechanical thrombectomy•Patient discharged with no known impact on cardiac function